Proceso de enfermería a una usuaria pediátrica con lupus eritematoso sistémico - Fimbres-Salazar, Karla Lizeth (Universidad de Sonora, 2019)
Introduction: The Nursing Process (NP) is the method applied by the nursing pro¬fessional to give user care, in the different stages of life cycle and during the different attention levels. This article presents a NP performed to a pediatric user who was hospitalized at a third level public pediatric hospital, with medical diagnosis systemic lupus erythematosus, lupus nephritis, deep vein thrombosis of the left pelvic limb and urinary tract infection. Materials and methods: assessment was made under Marjory Gordon is functional health patterns framework. It was used the Functional Health Patterns for Infant and Young Child Assessment Guideline. For the elaboration of the nursing care plan there were used the taxonomies North American Nursing Diagnosis Association (NANDA), Nursing Outcomes Classification (NOC), Nursing Interventions Classification (NIC).  Results: there were identified nine real nursing diagnoses and one at risk. It was concluded that nursing care in this disease and the associated pathologies leads to increase the quality of care and raise theoretical knowledge in autoimmune diseases.